One well : the story of water on Earth - Strauss, Rochelle, 1967-; Woods, Rosemary (A & C Black : Kids Can Press, 2007)
Tells the story of Earth's water, introducing the concept of the planet's water as being contained in one well, and discussing the importance of water to survival of plants, animals, and people, recycling, access to water, pollution, and conservation.
Includes index.
6.4
3-6
Keywords: Water -- Juvenile literature; Water; Water